Energy absorption performance of braided basalt reinforced composite tubes under axial loads - Roslan, Mohd Nazrul (2018)
The thin-walled composite tube is recognised as a potential replacement for thin-walled metal tubes in light-weight structures. In higher load-bearing structures, thick-walled composite tubes have more advantages compared to thin-walled composite tubes. However, thick-walled composite tubes use more material, thus resulting in additional weight to the structure. Therefore, a decent design of fibre reinforced sandwich composite tube with polymer foam-core could have a higher potential to provide both demands of high energy absorption capacity as well as light-weighting structure. Due to the recent environmental awareness, natural basalt fibre has been getting more demand and interest from preform manufacturers. Hence, the aim of this research is devoted to the investigation of energy absorption performance of novel and eco-friendly braided basalt composite tubes associated with axial crushing loadings. A series of thin-walled and sandwich composite tubes were fabricated using braided basalt/epoxy composite and expanded polyurethane foam. The axial crushing tests of these tubes under quasi-static and impact loads were carried out. A numerical model of sandwich tube with the highest energy absorption capability obtained experimentally was developed and validated with the experimental result. The main finding shows that sandwich tubes have better crushing control than thin-walled tubes under a dynamic impact loading. The result implies that there is an approximately 30% drop in value of crush force efficiency of thin-walled tubes under quasi-static compared to dynamic crushing, while sandwich tubes have sustained values. The experimental result also reveals that the basalt composite tube with a ±45º braid angle has the highest crushing performance compared to other braid orientations. The numerical model of sandwich tube (±45º/core/±45º) was validated with experimental result in accordance to the scopes and parameters used in this study.